2022 Fertilizer Station Weather Report - Matthew Sittel (Kansas Agricultural Experiment Station Research Reports, 2023)
This report includes the annual summary of precipitation and temperatures from 2022 at the research locations represented in the 2023 fertilizer report.
Keywords: Kansas State experiment fields; 2022 growing season weather; Kansas weather; fertilizer research